Teaching English language through British culture and its main features - Yigitaliyeva , Muxlisa (The Lingua Spectrum, 2025)
This article explores the integration of British culture into English language teaching and its significance. It highlights how understanding British traditions, values, and social norms enhances learners’ ability to comprehend the language in its cultural context. The use of British literature, idioms, accents, and historical events makes the learning process more engaging and meaningful. Moreover, cultural awareness improves communication skills and prepares learners for global interaction. By incorporating British culture into language instruction, educators can foster a deeper appreciation and understanding of the English language among students.